The evaluation of the matters regarding the production of biographical films in Turkish cinema from the perspective of audience, ethics, and copyright issues - OKUMUŞ, MUHAMMED SAMİ (My University, 2023)
This study aims to evaluate the interest of Turkish audiences in biographical film productions of historical figures or artists, which have been produced with big budgets since 2008, as well as the ethical values and copyright issues that cause legal processes during the production phase. In this context, the motivation for the production of such biographical works, which have increased in number especially in recent years, what kind of dramatic structure they deal with, the reflection of audience appreciation on the relevant productions, box office receipts, and their impact on the history of Turkish Cinema are analyzed. In order to access the information in the box office revenues section of the study, only the films released in movie theaters were focused on, and the films released on OTT platforms were excluded from the evaluation in this context. From this perspective, the following film projects were analyzed: Cars of the Revolution (2008), The Butterfly\"s Dream (2013), Ayla: The Daughter of War (2017), Müslüm (2018), Pocket Hercules: Naim Süleymanoglu (2019), Bergen (2022), Kesişme: İyi ki Varsın Eren (2022), Bandırma Missile Club (2022) and Prestij Meselesi (2023). Although it was not the most watched film in terms of the number of viewers, Bergen ranked first with ₺160,057,802, the highest box office revenue in the history of Turkish cinema. The second place among these productions was followed by Müslüm with ₺84,601,438 and the third place was taken by Ayla with ₺66,055,256. As is evident from the box office receipts, Turkish cinema audiences have developed an increasing interest, sensitivity, and sympathy for biographical stories over the years by the strict ties of the Yeşilçam tradition. The study also provides detailed information about the paths and policies followed by the producers of the biographical films.

Bu çalışma, ürk sinema film izleyicilerinin 200 ’den günümüze büyük bütçelerle ele alınan tarihi kişilik ya da sanatçıların biyografik tarzda ele alınan film yapımlarına ürk seyircilerin ilgisinin yanı sıra yapım aşamasında etik değerlerin ve hukuki süreçlere sebebiyet veren telif meselelerinin değerlendirilmesini amaçlamaktadır. Bu minvalde, özellikle sayıları son yıllarda artan bu tarz biyografik çalışmaların üretilme motivasyonu, ne tarz bir dramatik yapıda ele alındıkları, seyirci beğenisinin ilgili yapımlara yansıması, gişe hasılatları ve ürk Sinema tarihine etkileri analiz edilmiştir. Çalışmanın, gişe hasılatları bölümündeki bilgilere ulaşımı için sadece sinema salonlarında gösterimi yapılan filmlere odaklanılmış, O platformlarda gösterime giren filmler bu kapsamda değerlendirme dışı bırakılmıştır. Bu bakış açısıyla, Devrim Arabaları (2008), Kelebeğin Rüyası (2013), Ayla (2017), Müslüm (2018), Cep Herkülü aim Süleymanoğlu (2019), Bergen (2022), Kesişme: İyi ki Varsın Eren (2022), Bandırma Füze Kulübü (2022) ve Prestij Meselesi (2023) isimli sinema film projeleri ele alınmıştır. Seyirci sayısı bakımından en çok izlenen film olamasa da ürk sinema tarihinde en yüksek gişe hasılatı yapan Bergen filmi, ₺160.057. 02 ile ilk sıraya yerleşmiştir. Bu yapımlar arasında ikinciliği ₺ 4.601.43 gelirle Müslüm filmi takip etmekte, üçüncü sırada da ₺66.055.256 gişe geliriyle Ayla filmi yer almaktadır. Gişe hasılatları üzerinden açıkça görüldüğü üzere, ürk sinema seyircisi Yeşilçam geleneğinin sıkı bağlarıyla yıllar içinde biyografik öykülere karşı giderek artan bir ilgi, hassasiyet ve sempati geliştirdiği görülmektedir. Çalışmada ayrıca, biyografik tarzda ele alınan filmlerin yapımcılarının izlediği yol ve politikalar hakkında da detaylı bilgilere yer verilmektedir.
Türk sineması’nda biografik film üretimine dair meselelerinin seyirci, etik ve telif açısından değerlendirilmesi
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); ürk Sineması; Sinema Endüstrisi; Biyografik Filmler; Gişe Hasılatları; Seyirci; Turkish Cinema; Cinema Industry; Biographic Films; Box Office Revenues; Audience